PEMOTRETAN PREWEDDING STYLE BALI MODIFIKASI DENGAN TEKNIK ARTIFICIAL LIGHT - Suardika, I Made; Nindhia, Cokorda Istri Puspawati; Candrayana, Ida Bagus (Lp2mpp Isi Denpasar - Ps. Fotografi, 2023)
Artificial light is light that is intentionally made or created by humans for photographic purposes,such as flash lights, studio lights, fire etc. In photography light also becomes one part which will later determine the result of the image taken. The Final Task is expected to provide knowledge to the wider public of the importance of lighting to the results of a photographic work and development tugas development that can be created from such lighting effects, so that it can produce a more interesting photo work according to the characters to be highlighted in the work tebutrebut, so that society is acceptable in general. The implementation methods used on solving intern case objects exist 2 which are Observation Method and Interview Method. The results that have been obtained during the MBKM Internship/Work Practice are written works and photographic works. In this photographic work, the author displays the photographic work according to the charge of knowledge, the charge of skill, and the charge of technology.